The Inhibition Effect of Green Microalga Ethanol Extract (Nannochloropsis Oculata) on The Number of Bacteria Streptococcus Mutans (In Vitro) - Eriza Juniar; Yulie Emilda Akwan (Denta Journal Kedokteran Gigi, 2021)
Background: Antibacterial is a substance produced by a microorganism, which has the ability to inhibit growth or kill other microorganisms. Antibacterial activity is measured in vitro to determine the potency of an antibacterial agent in a solution, its concentration in body fluids or tissues, and the susceptibility of certain microorganisms to certain concentrations of drugs. Purpose: The purpose of this research was to find the power of extract ethanol Nannocholoropsis oculata as an alternative antibacterial causes of the growth of the caries which is Streptococcus mutans. Material and methods: extract ethanol. Nannocholoropsis oculate divided into three parts of concentration 1,5%, 2% and 2,5%, Chlorhexidine 0,12% as a control, culture bacteri Streptococcus mutans with McFarland 0.5 standart. The metode used in this study was One way analysis of varians (ANOVA), but first it had to be a homogenius test and a normalitas test. Result: The result of this study showed that no barrier power at concentration 1,5%, 2% and 2,5%. Conclucion: The result showed no inhibition in the three observed groups of 1.5%, 2%, and 2.5% of extract ethanol Nannochloropsis oculate. This meant that this article cannot prove the inhibition characteristic of Nannochloropsis oculate. This may be because the concentration of the extract Nannochloropsis oculata used in this study was too small. Henceforth, it is necessary to conduct research with a higher concentration of extract. On the other hand, the positive control group, using 0.12% Chlorhexidine solution, showed an inhibition characteristic while the negative control group, using 1 % of DMSO showed no inhibition.